Coexistence of primary myelofibrosis and chronic lymphocytic leukemia - Burgstaller S (Dove Medical Press, 2014)
Sonja Burgstaller, Josef Thaler Klinikum Wels-Grieskirchen, Abteilung für Innere Medizin IV, Wels, AustriaAbstract: Coexistence of two hematologic malignancies in one patient is generally a rare phenomenon. The topic of this article is the coincidence of primary myelofibrosis and chronic lymphocytic leukemia, which has been reported up to now in only 16 patients. In summary, simultaneous detection of both diseases was notable in half of the patients at presentation. In the case of a subsequent diagnosis of both disorders, primary myelofibrosis preceded the lymphoproliferative disease in the majority of patients. The clinical course seems to be more benign than for each disorder itself. A substantial proportion of patients did not require any treatment at all. Knowledge about the pathogenetic mechanisms, treatment approaches, and prognosis of these patients is limited.Keywords: primary myelofibrosis, chronic lymphocytic leukemia, coexistent